Community response to aquifer development: distinct patterns in India's alluvial and hard rock aquifer areas - Shah, Tushaar (Wiley, 2012)
The boom that India has experienced in groundwater irrigation is only weakly related to the availability of groundwater resources, long-term recharge rates and even availability of surface canal infrastructure. Dependence on groundwater has increased in rich alluvial aquifers with ample storage as well as in poor hard rock aquifers with limited storage. The socioeconomic and environmental impacts of the over-exploitation of groundwater are also equally pervasive. This paper shows that some, though not all, responses to groundwater over-development from farming communities are different in 'thick' alluvial aquifer areas from 'thin' hard rock aquifer areas. In the former, users fail to comprehend their interdependence, and consequently, to behave like an 'aquifer community' sharing a limited resource. As individual users, they engage in competitive deepening of boreholes to chase declining water levels. In arid alluvial areas, there is no sign of groundwater users trying either supply- or demand-side initiatives to make groundwater use sustainable. In contrast, many hard rock aquifer areas in India are seeing spontaneous initiatives from farmers, communities, NGOs and other players to cope with or counter aquifer depletion, mostly by individual or group efforts to increase groundwater recharge, but less so by making and enforcing rules to limit withdrawals.